Heparin Therapy Improving Hypoxia in COVID-19 Patients – A Case Series - Negri, Elnara Marcia; Piloto, Bruna Mamprim; Morinaga, Luciana Kato; Jardim, Carlos Viana Poyares; Lamy, Shari Anne El-Dash; Ferreira, Marcelo Alves; D’Amico, Elbio Antonio; Deheinzelin, Daniel (Frontiers in Physiology, 2020)
INTRODUCTION: Elevated D-dimer is a predictor of severity and mortality in COVID-19 patients, and heparin use during in-hospital stay has been associated with decreased mortality. COVID-19 patient autopsies have revealed thrombi in the microvasculature, suggesting that hypercoagulability is a prominent feature of organ failure in these patients. Interestingly, in COVID-19, pulmonary compliance is preserved despite severe hypoxemia corroborating the hypothesis that perfusion mismatch may play a significant role in the development of respiratory failure. METHODS: We describe a series of 27 consecutive COVID-19 patients admitted to Sirio-Libanes Hospital in São Paulo-Brazil and treated with heparin in therapeutic doses tailored to clinical severity. RESULTS: PaO2/FiO2 ratio increased significantly over the 72 hours following the start of anticoagulation, from 254(±90) to 325(±80), p=0.013, and 92% of the patients were discharged home within a median time of 11 days. There were no bleeding complications or fatal events. DISCUSSION : Even though this uncontrolled case series does not offer absolute proof that micro thrombosis in the pulmonary circulation is the underlying mechanism of respiratory failure in COVID-19, patient’s positive response to heparinization contributes to the understanding of the pathophysiological mechanism of the disease and provides valuable information for the treatment of these patients while we await the results of further prospective controlled studies.